Implementation of Local Wisdom in Stopping Prosecutions Based on Restorative Justice - Jungkung Madyo, Nurcahyo (KnE Social Sciences, 2023)
The Constitution of the Republic of Indonesia guarantees certainty, order, and legal protection for every citizen. Crime Statistics in 2021 showed that the number of criminal incidents in 2020 was 247,218 incidents. During the period from 2011 to 2018, theft was the most common crime in villages/the rural community in Indonesia, reaching more than 36-45% of all crimes. The term ”law blunts upwards, sharply downwards” is still often heard as a criticism of the government from justice seekers, especially regarding law enforcement against crimes of a minor or minor nature, such as theft in rural communities. The research method used is normative juridical with a historical approach, a case approach, and a conceptual approach, with a qualitative juridical analysis of legal materials. The results of this study argue that the adoption of the value of local wisdom can be beneficial for the renewal of Indonesian criminal law. The form of renewal is the formation of criminal procedural law to stop the prosecution of light cases. The basis for its implementation can use the theoretical basis of restorative justice, the principle of ultimum remedium, and the principle of fast, simple, and low-cost justice. The form of implementation of local wisdom in the termination of prosecutions is community reparation boards and citizen panels. Keywords: restorative justice, local wisdom, criminal